2004
DOI: 10.1007/s00464-003-9310-7
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy-assisted distal gastrectomy for early gastric cancer in obese and nonobese patients

Abstract: The only difference between our two study groups was that LDG required a longer operating time in obese patients; morbidity and length of hospital stay were not increased. Thus, we believe that LDG is likely to become the treatment of choice for obese patients with early gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
51
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 18 publications
(19 reference statements)
3
51
1
1
Order By: Relevance
“…Noshiro et al [24] have shown that LADG for heavier patients was associated with more technical difficulties and the disadvantages of a longer operation time and delayed recovery of bowel activity, compared with findings in normal-weight patients. In the report of Yasuda et al [25], the operation time was longer in the obese group, but no differences were found in the other operative parameters. Our study showed that there were no statistically significant differences between our two BMI groups in age, sex, depth of tumor invasion, lymph node metastasis, operation time, postoperative leukocyte count, number of patients requiring transfusion, the time interval to first flatus, the postoperative hospital stay, and the postoperative complications.…”
Section: Discussionmentioning
confidence: 76%
“…Noshiro et al [24] have shown that LADG for heavier patients was associated with more technical difficulties and the disadvantages of a longer operation time and delayed recovery of bowel activity, compared with findings in normal-weight patients. In the report of Yasuda et al [25], the operation time was longer in the obese group, but no differences were found in the other operative parameters. Our study showed that there were no statistically significant differences between our two BMI groups in age, sex, depth of tumor invasion, lymph node metastasis, operation time, postoperative leukocyte count, number of patients requiring transfusion, the time interval to first flatus, the postoperative hospital stay, and the postoperative complications.…”
Section: Discussionmentioning
confidence: 76%
“…Longer operation times for obese patients are predictable and have been reported repeatedly [8][9][10]. However, fewer numbers of retrieved LNs in obese patients is an unexpected finding that has rarely been reported.…”
Section: Discussionmentioning
confidence: 92%
“…Many largescale studies have repeatedly demonstrated that obesity influences surgical outcomes after gastric cancer surgery [7,[19][20][21]. Conversely, studies focusing on LAG have shown that obesity does not increase surgical morbidity [8][9][10]. However, the limited numbers of patients in these studies (usually fewer than 100) make these results very inconclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have suggested that obesity does not affect postoperative morbidity or mortality. 13,14 However, a longer operation time has been noted in obese patients. 7 This study evaluated the postoperative complication rate after laparoscopic distal gastrectomy and the safety of laparoscopic distal gastrectomy in patients with a high BMI.…”
Section: Discussionmentioning
confidence: 99%